Replacement of Soybean Meal Flour with Fermented Moringa (Moringa oleifera) Leaves Flour on Catfish (Clarias sp.) Feed - Yusup, Maulid Wahid; Febri Haryanti1, Indri; Santoso, Limin; Elisdiana, Yeni; Susanti, Oktora; Julian, David; Kholiqul Amiin, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Clarias sp. represent one of the most prominent aquaculture commodities in Indonesia, but the challenge in catfish aquaculture is the production of feed because it is highly vulnerable to imports. Therefore, Moringa (Moringa oleifera) leaves are considered as an alternative raw material for vegetable protein source-based catfish feed to reduce soybean imports. This research was conducted to examine the use of different proportions of Moringa oleifera fermented leaf meal in feed as substitute for soybean meal on the performance catfish (Clarias sp.). This study used a completely randomized design with five treatments and three repetition of feed A as a control (0% of fermented moringa leaves flour), feed B (75% of soybean meal flour + 25% of fermented moringa leaves flour), feed C (50% of soybean meal flour + 50% of fermented moringa leaves flour), feed D (25% of soybean meal flour + 75% of fermented moringa leaves flour) and feed E (100% of fermented moringa leaves flour). Based on the data, the supplementation of fermented moringa meal with E feed had a significant increase in absolute weight growth, specific growth rate, feed conversion rate, protein retention and fat retention and a decrease in protein efficiency ratio. The fermented moringa leaves flour with the composition of 100% can be used in catfish feed as a substitution for soybean meal flour with an average absolute weight growth is 13,16±2,54 – 15,76±1,03 g.